Antiphospholipid Antibody Syndrome : From Bench to Bedside - Meroni, Pier Luigi (Rare Diseases of the Immune System, 2015)
This book, part of the series Rare Diseases of the Immune System, offers comprehensive, up-to-date coverage of the pathophysiology and management of the antiphospholipid syndrome (APS). Immunologic and genetic aspects are discussed and the pathogenic mechanisms responsible for such phenomena as APS-mediated thrombosis and pregnancy loss or complications are explained. The main clinical manifestations and classification criteria are described and diagnostic tools, identified. Close attention is paid to the nature of the involvement of other organs or organ systems in APS, including the nervous, endocrine, hematologic, cardiovascular, and gastrointestinal systems, the kidney, the skin, and the eye. Specific chapters describe the treatment of the different symptoms, the preventive therapies of value in avoiding recurrences, and innovative treatment approaches. The authors are senior experts in the field who are aided by younger fellows, ensuring that the book is also educationally oriented. This handy volume will be a valuable tool for postgraduates in training and professionals wishing to extend their knowledge of this specific syndrome.